Quality of life, sleepiness and depressive symptoms in adolescents with insomnia: a cross-sectional study - Amaral, Maria Odete Pereira (2017)
Objectives To determine the prevalence of insomnia in a sample of Portuguese adolescents and assess its repercussions on HRQoL, daytime sleepiness and depressive symptomatology. Design We carried out a cross-sectional school-based study evaluating students from Viseu. Location Students from twenty-six public secondary schools in the county of Viseu, Portugal. Participants Of 9237 questionnaires distributed, 7581 were collected (82.1%). We excluded from analysis all questionnaires from adolescents younger than 12 or older than 18 years of age (211) and unfilled forms (451). The sample comprised 6919 adolescents, the 7th to 12th grade, from 26 public secondary schools. Interventions None. Measurements Data gathering was done using a self-applied questionnaire. Insomnia was defined based on the Diagnostic and Statistical Manual of Mental Disorders – IV criteria. HRQoL was evaluated with the Quality of Life Health Survey SF-36, depressive symptomatology with BDI-II and daytime sleepiness with the Epworth Sleepiness Scale. Results Prevalence of insomnia was 8.3% and the prevalence of adolescents with symptoms of insomnia without daytime impairment (disturbed sleepers) was 13.1%. HRQoL was significantly reduced among adolescents with insomnia compared to normal sleepers (p < 0.001) and even when compared to disturbed sleepers (p < 0.001). There was an increase in daytime sleepiness from normal sleepers to disturbed sleepers and to adolescents with insomnia (p < 0.001). There was also an increase in the prevalence and severity of depressive symptoms (p < 0.001). Conclusions Our results show that insomnia is associated with a significantly lower health related quality of life among adolescents.